Hilbert–Schmidt Measure of Pairwise Quantum Discord for Three-Qubit X States. Issue 2 (October 2015) - Daoud, M.; Laamara, R. Ahl; Seddik, S.
Abstract : The Hilbert–Schmidt distance between a mixed three-qubit state and its closest state is used to quantify the amount of pairwise quantum correlations in a tripartite system. Analytical expressions of geometric quantum discord are derived. A particular attention is devoted to two special classes of three-qubit X states. They include three-qubit states of W, GHZ and Bell type. We also discuss the monogamy property of geometric quantum discord in some mixed three-qubit systems.